Validation of the Job Crafting Scale in Latin American Workers - Gutiérrez, Oscar Iván; Polo Vargas, Jean David; Vargas Montealegre, Alba Ruth; Zumárraga Espinosa, Marcos; Ramírez Ocaña, Ximena; Segovia Marín, Valeria; Calderín Salgado, Lina Margarita (Anales de Psicología / Annals of Psychology, 2022)
In this study, the psychometric properties of the Spanish version (Bakker et al., 2018) of the Job Crafting scale of Tims et al. (2012), was analyzed in a Latin American population. We applied the scale to a sample of 903 employees (42.6% women & 57.4% men) from Colombia and Ecuador. Reliability and validity were examined. The results of the confirmatory factor analysis showed an adequate fit both in Colombia (CFI = .916, TLI = .900, IFI = .917, RMSEA = .060) and in Ecuador (CFI = .918, TLI = .903, IFI = .919, RMSEA = .064), in the four-factor structure of the original scale. Evidence of validation, related to criterion for psychological well-being for the dimensions of increasing structural resources and increasing challenging demands, was found. The Spanish version of the scale demonstrates its usefulness for research in the Latin American context.